To verify which expression is equivalent to \((x−5)(x−3)\), we can use the Distributive Property (also known as the FOIL method for binomials).
-
First: Multiply the first terms: \[ x \cdot x = x^2 \]
-
Outer: Multiply the outer terms: \[ x \cdot (-3) = -3x \]
-
Inner: Multiply the inner terms: \[ -5 \cdot x = -5x \]
-
Last: Multiply the last terms: \[ -5 \cdot (-3) = 15 \]
Now, combine all these results: \[ x^2 - 3x - 5x + 15 = x^2 - 8x + 15 \]
So, the equivalent expression is: \[ x^2 - 8x + 15 \]
Therefore, the correct response is: x² − 8x + 15.